International Accounting and Reporting Issues - 2001 Review - United Nations Conference on Trade; Development (United Nations, 2002)
This report contains proceedings of the eighteenth session of the International Standards of Accounting and Reporting (ISAR). The deliberations focused on the categorization of Small and Medium-sized Enterprises, user friendly accounting and reporting frameworks, and difficulties in their implementation.